PEMBINAAN INFAQ DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SEKOLAH MENENGAH ATAS ISLAM TERPADU (SMAIT IQRA’) KOTA BENGKULU - Rahwani, Indah; Nurlaili; Ulum, Bakhrul (Yayasan Darussalam Bengkulu, 2020)
It forms religious character and as the application of human obedience to the Lord and human concern with others as a form of worship. It has been suggested that this development would make human beings better. The goal in this study is to describe the planned infaq coaching character of small protege SMAIT IQRA’ Bengkulu City, as well as to describe the execution of infaq's religious character at SMAIT IQRA' Bengkulu City, and to describe the evaluation of the infaq's fostering of the religious character of the protege at SMAIT IQRA’ Bengkulu City. The study uses field research with a qualitative approach. The method used was descriptive research. The subject of this study is the infaq coaching teacher and student representative at SMAIT IQRA’ the City of Bengkulu. The object of this study is the infaq development of the religious character of a protege at SMAIT IQRA’ Bengkulu City. Data collection techniques using observation, interviews, and documentation. Based on research, the infaq development in the form of the religious character of students at SMAIT IQRA' Bengkulu City includes 1) the infaq planning to build with the proposed headmaster and approved teacher council, 2) the performance and evaluation of the infaq's execution, the target is slimed.